Nonlinear finite element study on the improvement of shear capacity in reinforced concrete T-Section beams by an alternative diagonal shear reinforcement. (1st August 2016) - Demir, Aydin; Caglar, Naci; Ozturk, Hakan; Sumer, Yusuf
Highlights: New shear reinforcement configuration (DSR) is proposed as an alternative technique to improve shear capacity of RC beams. A nonlinear finite element study is performed by considering two tested RC beams with flexural and shear failure modes. The tests results are first verified numerically then DSR is included to existing FE model to make a parametric study. When the proposed DSR is included, a significant increase in shear and ductility capacity of RC beams is achieved. The proposed DSR is also an easy and economical technique that can exhibit great cyclic performance under seismic loads. Abstract: In the study a new shear reinforcement configuration named as diagonal shear reinforcement (DSR) is proposed as an easily applicable, economical and alternative technique to improve the shear capacity and ductility of shear critical reinforced concrete (RC) beams under monotonic and cyclic loadings. For this objective a numerical nonlinear finite element (FE) study is performed by considering two tested beams with flexural and shear failure modes. These two tests results are first verified numerically then DSR is included to existing FE model to start a parametric study for highlighting the efficiency of proposed DSR shear reinforcement configuration. The numerical results demonstrate that there is a significant increase in shear and ductility capacity of RC beams when proposed DSR is included. Moreover, with an increase in diameter and yield strength of DSR, the shear capacity further improves and failure mechanism shifts from shear to flexure. Thus, more ductile behavior for shear critical RC beams is achieved by the proposed DSR reinforcement configuration.